Ensino de matemática para surdas e surdos: contribuições de docentes de um centro de atendimento educacional especializado - Marmontelo, Jocione Aparecida (2022)
The educational inclusion of deaf students has been the subject of discussions among educators and researchers. More specifically, in Brazil, the current National Policy for Special Education (within the Inclusive Education frame) is designed to ensure that such inclusion takes place. One of the actions of this policy is the offer of Specialized Educational Service, which is part of the comprehensive training, acting through pedagogical support provided after standard mandatory schooling hours. This action aims to help students with disabilities in their educational process by identifying, developing and organizing pedagogical and accessibility resources that dismantle potential obstacles to the full participation of these students in educational practices. This research aims to investigate and analyze the actions, interventions and didactic-pedagogical strategies that teachers at a Specialized Educational Service Center develop to complement the Mathematics training of deaf students. The methodological approach used was qualitative. The data analysis used was the "Content Analysis", through an interpretive-comprehensive perception of the data collected in the semi-structured interviews carried out with teachers who teach Mathematics in a Specialized Educational Service Center (CAEE). We also used the strategy of document analysis for class plans, school roaming notebooks, activity reports and other plans built and used since 2010. The data covered the statements referring to the experiences and teaching strategies used by the interviewed teachers. Three categories of analysis were listed: (1) Didactic-pedagogical strategies; (2) Mathematics teaching and learning processes and (3) the partnership between the Specialized Educational Service and standard schools. As a result of the present research, one can observe that, for the teaching of Mathematics, teachers transmit the content using LIBRAS (acronym for Brazilian sign language) on a first instance, followed by complex didactic-pedagogical strategies through the use of visual resources that facilitate the learning of deaf students. Another result to be highlighted was the importance given by the teachers regarding the need for a partnership between the CAEE and the regular school, aiming to follow the educational development of the student and to assist the common school teachers in the elaboration of strategies and the creation of scholar material. From the results obtained, we produced a booklet containing didactic-pedagogical guidelines and suggestions for teachers and professionals working in the education of deaf people.